Space Telescopes and Instrumentation 2012: Optical, Infrared, and Millimeter Wave 2012
DOI: 10.1117/12.926843
|View full text |Cite
|
Sign up to set email alerts
|

Progress toward BLISS, the background-limited infrared-submillimeter spectrograph for SPICA

Abstract: We are developing the Background-Limited Infrared-Submillimeter Spectrograph (BLISS) for SPICA to provide a breakthrough capability for far-IR survey spectroscopy. The 3.2-meter, actively-cooled (T<6K) SPICA telescope allows mid-IR to submm observations which are limited only by the natural backgrounds, and BLISS is designed to operate near this fundamental limit. BLISS-SPICA provide a line sensitivity of 10 −20 W m −2 , thereby enabling spectroscopy of dust-obscured galaxies at all epochs back to the first bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…The TES bolometers designed for the SAFARI instrument on the SPICA satellite have saturation powers of a few femtoWatts and phonon NEPs on the order of 10 W Hz 19 - (Roelfsema et al 2012). Achieving these sensitivities requires very good control of stray light and this has recently been demonstrated by groups at JPL and SRON (Bradford et al 2012;Suzuki et al 2016). In particular, the measurements at SRON showed that detectors with resistive absorbers had excess noise above the phonon noise limit in a first test while those without the absorbers reached the phonon noise.…”
Section: Excess Noise In Tes Detectorsmentioning
confidence: 99%
“…The TES bolometers designed for the SAFARI instrument on the SPICA satellite have saturation powers of a few femtoWatts and phonon NEPs on the order of 10 W Hz 19 - (Roelfsema et al 2012). Achieving these sensitivities requires very good control of stray light and this has recently been demonstrated by groups at JPL and SRON (Bradford et al 2012;Suzuki et al 2016). In particular, the measurements at SRON showed that detectors with resistive absorbers had excess noise above the phonon noise limit in a first test while those without the absorbers reached the phonon noise.…”
Section: Excess Noise In Tes Detectorsmentioning
confidence: 99%